2015
DOI: 10.1515/intag-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of physical, mechanical, and structural seed properties of pepper cultivars

Abstract: A b s t r a c t. The aim of the present study was to determine various physical, mechanical, and structural characteristics of seed of pepper cultivars Yağlık Kapya, Demre Sivri, Yalova Carliston, Kandil Dolma, and Cin Sus Yediveren, which are grown extensively in Turkey, with initial moisture content ranging between 7.03 and 7.21% (w.b.). Width, length, and thickness were found to be in the range of 3.00-3.72, 3.43-4.40, and 0.66-0.82 mm, respectively. It was revealed that sphericity of the seeds of Yağlık Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…All of these studies have indicated an increase in static and kinetic friction along with an increase in moisture for plant granular materials. Many authors have taken into account the type of construction material as a factor influencing the value of the force of friction in their works [10,12,16,17,19,[21][22][23][24]. A further factor whose influence on force of friction has been studied is the speed of motion across a surface.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies have indicated an increase in static and kinetic friction along with an increase in moisture for plant granular materials. Many authors have taken into account the type of construction material as a factor influencing the value of the force of friction in their works [10,12,16,17,19,[21][22][23][24]. A further factor whose influence on force of friction has been studied is the speed of motion across a surface.…”
Section: Introductionmentioning
confidence: 99%
“…This property is important in the development of the hopper and design of bark for this seed. The Ø of PN and PK was higher than that reported for pepper 51-57% (Alibas and Koksal 2015), pumpkin 45.36% (Rodrı ´guez-Miranda et al 2016), melon 36.85% (Mansouri et al 2017), peanut 51.6% (Aydin, 2007), kidney bean 62.12% (Wani et al 2017) and faba bean 63.47% (Altuntas ¸and Yıldız, 2007), being more spherical than these.…”
Section: Geometric Propertiesmentioning
confidence: 62%
“…The wall surface had a more significant influence than moisture content in rolling friction (Table 4). Plywood was reported to offer higher friction for pepper seed, jatropha seed, pigeon pea, gram, canola meal, and neem nut, and the coefficient of friction increased with moisture content (Alibas and Koksal, 2015;Dutta et al, 1988;Garnayak et al, 2008;Kulkelko et al, 1988;Shepherd and Bhardwaj, 1986;Visvanathan et al, 1996). 2.…”
Section: Resultsmentioning
confidence: 99%